Numerical Study of Sedimentation and Flow Pattern at the Open Channel Intake - Rana Al-Zubaidy; Ali N. Hilo (Wasit Journal of Engineering Sciences)
Generally, open channel lateral intake structures are extensively used in the water and environmental projects. The passing flow at side intakes is mostly turbulence containing vertical and horizontal spiral currents causing sediment problems. The flow separation region in the intake channel is critical for sediment and water distribution during the diversion. It denotes a large reduction in the possible breadth of the lateral branch's incoming flow, as well as a place where sediment has collected, obstructing the deviated flow.